2008
DOI: 10.2341/07-134
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Traditional and Low Sensitivity Whiteners

Abstract: SUMMARYThis placebo-controlled, double-blind randomized clinical trial compared five 10% carbamide peroxide tooth whitening formulations. Three products contained varying concentrations of potassium nitrate as desensitizers. One contained no desensitizers and one was a placebo. During the two weeks of active bleaching, participants used a daily diary to record the number of days of sensitivity from hot, cold, gums, tongue and/or throat. The total number of days of sensitivity experienced by the participants in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 12 publications
5
58
0
1
Order By: Relevance
“…The selection of this method was based on the fact that it is an easy, fast, and satisfactory method that has been used in several investigations. [16][17][18] The validity and reliability of this color evaluation method was confirmed by a recent study. 19 The authors reported that despite the subjectivity of the method, visual assessment of tooth color using the Vitapan Classical shade guide is a valid method, with good reliability for differentiating between dark and light colors.…”
Section: Discussionmentioning
confidence: 57%
“…The selection of this method was based on the fact that it is an easy, fast, and satisfactory method that has been used in several investigations. [16][17][18] The validity and reliability of this color evaluation method was confirmed by a recent study. 19 The authors reported that despite the subjectivity of the method, visual assessment of tooth color using the Vitapan Classical shade guide is a valid method, with good reliability for differentiating between dark and light colors.…”
Section: Discussionmentioning
confidence: 57%
“…The Vitapan Classical guide (Vita Zahnfabrik RauterGmbH H. & Co, BädSackingen, Germany) was organized according to a scale of values numbered 1-16. 3,4,24,25 The first in-office bleaching session was performed in the maxillary arch. 3,24 A resin barrier (Top Dam, FGM, Joinville, Brazil) and a lingual / lip retractor (Arcflex, FGM, Joinville, Brazil) were used.…”
Section: Day 15mentioning
confidence: 99%
“…24 Values ranging from 1 (B1) to 16 (C4) were determined for each Vitapan Classical Guide shade, and the color change was assessed based on the difference between the initial and final colors. 25 A statistical analysis was performed to determine the sensitivity reported by the patients, and the color changes were analyzed subjectively based on the Vitapan scale. The results were analyzed applying the Shapiro-Wilk, Wilcoxon, Kruskal-Wallis and Mann-Whitney tests at a significance level of α = 0.05.…”
Section: Day 15mentioning
confidence: 99%
“…Although the gel without desensitizing agent that was used in the current study had no active desensitizing agent, it may have stimulated salivary flow, which might have reduced the sensitivity given that dehydration is one of the causes of sensitivity. 25 However, Tay and others 8 found that the intensity of sensitivity was significantly higher in the placebo gel group than in a group of participants who used fluoride/potassium nitrate gel. This might be attributed to the fact that the desensitizing gel was applied for 10 minutes before the whitening procedure; in addition, there was a possible dual effect of using both fluoride and potassium nitrate.…”
Section: Tooth Sensitivity Evaluationmentioning
confidence: 99%
“…This is in agreement with previous studies that used fluoride, 8 CPP-ACP materials, 16 or potassium nitrate and sodium fluoride. 25 …”
Section: Tooth Shade Stabilitymentioning
confidence: 99%